ICE-SHEET DYNAMICS OF WARTA GLACIATION (SAALE) IN THE MARGINAL ZONE OF KNYSZEWICZE AREA, NORTHEASTERN POLAND - Rychel, Joanna; Woronko, Barbara; Karasiewicz, Mirosław T.; Szymczuk, Paweł; Morawski, Marcin (2017)
The paper presents a research on a marginal zone near Knyszewicze in the southern part of Sokółka Hills (northeastern Poland). Terminal moraine hills arearranged amphitheatrically in a lobal pattern. Dynamics of the Knyszewicze frontal ice-sheet lobe during the Saale Glaciation and successive stages of the marginal zone near the village of Knyszewicze were reconstructed based on sedimentary and geomorphological analysis, using a digital elevation model and morpholineaments. Three main phases of the Knyszewicze glacial-lobe activity were identified including accumulation of glaciofluvial deposits, advances of the ice margin and ice-lobe retreat. Moraine hills developed at a stable ice-lobe terminus, initially as short end-moraine fans with the fol low ing se quence of lithofacies Gh-SGh-Sh or Gm-Gh-Sh. Such a sequence indicates cyclic sheet-floods. During a small but dynamic advance of the ice sheet terminus, these depos its were moved for ward and monoclinally folded, then furrowed with sloping faults due to horizontal pressure. Typ i cal thrust-block push moraines developed in this way. Ice sheet advance took place when permafrost was present in the substratum and very high water pressure occurred at glacial terminus. Inside a lobal configuration of moraines, there is a rich inventory of glacial forms with a classic terminal depression in the central part. Based on this landform pattern, their shape, rhythm and glaciotectonic disturbances, the land relief may be referred to as a hill-hole pair. The structure of Horczaki Knoll, deposited on the sub-Quaternary tectonic structure, significantly contributed to a development of this marginal zone.